Raynal's 'Histoire des deux Indes' - Courtney, C (Voltaire Foundation, 2017)
Histoire des deux Indes, was arguably the first major example of a world history, exploring the ramifications of European colonialism from a global perspective. Frequently reprinted and translated into many languages, its readers included statesmen, historians, philosophers and writers throughout Europe and North America. Underpinning the encyclopedic scope of the work was an extensive transnational network of correspondents and informants assiduously cultivated by Raynal to obtain the latest expert knowledge. How these networks shaped Raynal’s writing and what they reveal about eighteenth-century intellectual sociability, trade and global interaction is the driving theme of this current volume. From text-based analyses of the anthropology that structures Raynal’s history of human society to articles that examine new archival material relating to his use of written and oral sources, contributors to this book explore among other topics: • how the Histoire created a forum for intellectual interaction and collaboration; • how Raynal created and manipulated his own image as a friend to humanity as a promotional strategy; • Raynal’s intellectual debts to contemporary economic theorists; • the transnational associations of booksellers involved in marketing the Histoire; • the Histoire’s reception across Europe and North America and its long-lasting influence on colonial historiography and political debate well into the nineteenth century. Cecil Courtney and Jenny Mander, Introduction I. The theme of global exchange in the Histoire des deux Indes Stéphane Pujol, La logique des échanges dans l’Histoire des deux Indes Peter Jimack, Coconuts, spice and sugar: indolence, energy and social interaction in the Histoire des deux Indes Christian Donath, Apostles of the state: legitimate colonisation tactics in the Histoire des deux Indes Antonella Alimento, Entre rivalité d’émulation et liberté commerciale: la présence de l’école de Gournay dans l’Histoire des deux Indes Sylvana Tomaselli, On labelling Raynal’s Histoire: reflections on its genre and subject Daniel Droixhe, Y a-t-il vraiment une ethnologie chez Raynal? L’enfance de l’art américain dans les ‘Deux Indes’ Daniel Gordon, Uncivilised civilisation: Raynal and the global public sphere II. Mediating networks: the making and marketing of the Histoire des deux Indes Kenta Ohji, Raynal auto-compilateur: le projet d’une histoire politique de l’Europe moderne – des Mémoires historiques à l’Histoire des deux Indes Gilles Bancarel, Ecriture et information: aux sources du réseau de Raynal Gianluigi Goggi, La seconde édition de l’Histoire des deux Indes: relations entre libraires et stratégie de lancement dans les annonces des gazettes Ida Federica Pugliese, From antagonism to a common fate: Guillaume-Thomas Raynal and William Robertson Susanne Greilich, ‘Et moi suis-je sur des roses?’: l’Histoire des deux Indes entre l’historiographie espagnole, leyenda negra et discours anticolonial Ursula Haskins Gonthier, The ‘Supplément au journal de Bougainville’: representations of Native Canadians in the Histoire des deux Indes III. The Histoire des deux Indes and its network of readers Fredrik Thomasson, Raynal and Sweden: royal propaganda and colonial aspirations Reinier Salverda, Raynal and Holland: Raynal’s Histoire des deux Indes and Dutch colonialism in the age of Enlightenment Hans-Jürgen Lüsebrink, Controverses transatlantiques: contenus, enjeux et impact international de la Letter to the abbé Raynal (1782) de Thomas Paine Jennifer Tsien, Louisiana as a figment of the imagination: Raynal’s reflections on the French American colony Muriel Collart, L’Histoire des deux Indes et le Dictionnaire universel des sciences de Jean-Baptiste Robinet Philippe Barthelet, Raynal sous le feu de ses adversaires: l’exemple de Joseph de Maistre Georges Dulac, Un protestant languedocien admirateur de Raynal: l’Histoire des deux Indes dans le fonds Louis Médard de Lunel